Circle of Security Intervention for Parents of Children with Autism Spectrum Disorder. Issue 4 (December 2016) - Fardoulys, Claire; Coyne, Joe
Abstract : Circle of Security is an attachment‐based parenting intervention that aims to promote secure parent–child attachment relationships. The current study explored whether the Circle of Security intensive intervention resulted in increased attachment security (assessed before and after completing the intervention) for caregiver–child dyads with Autism Spectrum Disorder. The current study also explored caregivers' acceptance of the intervention by seeking client feedback and measured each caregiver's perceived sense of parenting competence. Two mothers each with a child under the age of 5 years diagnosed with Autistic Spectrum Disorder participated in the intervention. Results found one dyad shifted from avoidant to secure whilst the other dyad remained secure across time with some changes in behavioural dimensions. Each mother endorsed the intervention as highly valuable to her needs. Perceived parenting competence also increased post‐intervention for both mothers. Replication is recommended in order to generalise the results.